Monocrystal hierarchical pore ZSM-5 molecular sieve as well as preparation method and application thereof
By adding microporous and mesoporous template agents to the preparation process of ZSM-5 molecular sieve, a single crystal ZSM-5 molecular sieve with a multi-stage pore structure was prepared, which solved the diffusion limitation problem of existing ZSM-5 molecular sieve in application and improved the catalytic performance and service life.
Patent Information
- Application Number
- CN202311404616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ZSM-5 molecular sieve has diffusion limitations in application, resulting in a degradation of catalytic performance and a shortened service life.
A single crystal ZSM-5 molecular sieve with a multi-stage pore structure is prepared by adding microporous template agent and mesoporous template agent to the colloid, performing crystallization treatment and calcination.
It improves the diffusion performance of ZSM-5 molecular sieve and the accessibility of acid sites, extends the service life of the catalyst, and avoids the adverse effects of alkali treatment.
Smart Images

Figure CN119898790A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieve preparation, and more specifically to a single crystal multi-level pore ZSM-5 molecular sieve and a preparation method and application thereof. Background Art
[0002] The ZSM-5 molecular sieve synthesized by Mobil in 1960 is a new type of zeolite with MFI topological structure. The ZSM-5 molecular sieve is an orthorhombic system composed of crystals with unit cell parameters of a=2.01nm, b=1.99nm, c=1.34nm, belonging to the Pnma space group. The basic structural unit is composed of eight five-membered rings, which further form a wavy network layer with 10-membered rings, and finally form a three-dimensional pore structure: an elliptical straight pore parallel to the
[010] crystal plane (0.54×0.56nm) and an approximately elliptical sinusoidal pore parallel to the
[100] crystal plane (0.52×0.58nm), and the diameter of the intersection of the two pores is 0.9nm. The pores of the ZSM-5 molecular sieve are composed of its cavities, without cages or side pockets like MCM-22 and EU-1 molecular sieves. Compared with large-pore molecular sieves, the ZSM-5 molecular sieve exhibits lower coking rate and aging rate, and has a longer service life. The Si / Al ratio of molecular sieve can be adjusted from 9 to ∞. The change of Al content in the framework and the adjustment of Al distribution can adjust the acid properties of molecular sieve, so as to better adapt to different reaction systems. ZSM-5 molecular sieve is widely used as a catalyst in the fields of isomerization of n-butene to isobutylene, conversion of ethanol to aromatics, isomerization of xylene, disproportionation of toluene, etc.
[0003] The simple microporous structure and long diffusion path of ZSM-5 molecular sieve accelerate the deactivation of molecular sieve. The only microporous structure reduces the diffusion efficiency of reactant molecules in the pores. It is difficult for macromolecules to diffuse in the microporous channels, resulting in carbon deposition and eventually blocking the pores. The diffusion barrier of products in the micropores may lead to the occurrence of side reactions. In order to overcome the above shortcomings, many studies have improved the morphology, pore size, pore structure and particle size of ZSM-5 molecular sieves. Among them, the construction of a multi-level pore structure can enhance the diffusion rate of reactants and increase the accessibility of acid active sites, greatly improving the catalytic performance of ZSM-5 molecular sieves. The multi-level pore structure refers to the introduction of mesopores (2-50nm) or macropores (>50nm) connected to the micropores on the basis of retaining the original micropores of the molecular sieve. The entire pore system shows an orderly and multi-level arrangement to achieve rapid mass transfer and efficient reaction.
[0004] Teng Xue et al. used CTABr and HDA as dual templates to synthesize ZSM-5 molecular sieves with intercrystalline mesopores. The molecular sieves exhibited a larger specific surface area and mesopore volume, and showed good catalytic activity in the LDPE catalytic reaction (Microporous and Mesoporous Materials, 2017, 242: 190-199). However, the use of surfactants as mesoporous templates to synthesize products is prone to phase separation, and the quality of the synthesized multi-level pore molecular sieves is difficult to guarantee. Shouyi Li et al. used TPAOH post-treatment desiliconization to synthesize a ZSM-5 molecular sieve with a multi-level pore structure. The ZSM-5 molecular sieve with a multi-level structure increased the conversion rate from 30.7% to 78.2% in the dealkylation reaction of alkylphenols. The increased mesopores reduced the diffusion resistance of the reactant and product molecules inside the molecular sieve, avoided coking caused by excessive reaction, and extended the service life of the catalyst (Fuel Processing Technology, 2023, 246: 107759). However, the synthesized molecular sieve needs to be treated with alkali, which not only increases the cost of synthesizing the molecular sieve, but also has an adverse effect on the stability of the molecular sieve skeleton structure.
[0005] Therefore, it is very necessary to develop a method for preparing a ZSM-5 molecular sieve with a multi-level pore structure including micropores and mesopores with stable quality, so as to solve the problem of diffusion limitation of the existing ZSM-5 molecular sieve in application. Summary of the invention
[0006] The purpose of the present invention is to provide a single crystal multi-level pore ZSM-5 molecular sieve and a preparation method and application thereof, so as to solve the technical problem of diffusion limitation of ZSM-5 molecular sieve in the application in the prior art.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a method for preparing a ZSM-5 molecular sieve, comprising:
[0009] S1. Obtaining a colloid including an aluminum source, an alkali source, a silicon source, a microporous template, and a solvent;
[0010] S2. adding a mesoporous template to the colloid to obtain a mixture;
[0011] S3. The mixture is crystallized and calcined to obtain a ZSM-5 molecular sieve.
[0012] According to some embodiments of the present invention, the microporous template agent is selected from at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetrabutylammonium hydroxide, and n-butylamine.
[0013] According to some embodiments of the present invention, the microporous template is n-butylamine.
[0014] According to some embodiments of the invention, the mesoporous templating agent is poly(allylamine) (PHA).
[0015] According to some embodiments of the present invention, the weight average molecular weight M of the poly(allylamine) w It ranges from 10,000 to 70,000.
[0016] According to some embodiments of the present invention, the weight average molecular weight M of the poly(allylamine) w It ranges from 10,000 to 50,000.
[0017] According to some embodiments of the present invention, the weight average molecular weight M of the poly(allylamine) w It ranges from 10,000 to 30,000.
[0018] According to some embodiments of the present invention, the weight average molecular weight M of the poly(allylamine) w It is 12000 to 20000.
[0019] According to some embodiments of the present invention, the aluminum source is selected from at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide.
[0020] According to some embodiments of the present invention, the alkali source is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water.
[0021] According to some embodiments of the present invention, the silicon source includes at least one of silicon powder, silicon balls, silica gel, silica sol, sodium silicate (sodium silicate / water glass), silica alumina, silicate (such as methyl silicate, ethyl silicate or propyl silicate), silicon tetrachloride, silane, white carbon black, and diatomaceous earth.
[0022] According to some embodiments of the present invention, the solvent comprises at least one of water, methanol, ethanol, ethylene glycol, and glycerol.
[0023] According to some embodiments of the present invention, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as OH - The microporous template agent is R1, the mesoporous template agent is R2, the solvent is I, and the molar ratio of each raw material is: SiO2 / Al2O3=25-300, OH - / SiO2=0.05~0.5, R1 / SiO2=0.01~0.8, I / SiO2=3~300; the mass ratio of the mesoporous template agent to the silicon source is mR2 / mSiO2=0.01~0.8.
[0024] According to some embodiments of the present invention, SiO2 / Al2O3=30-65.
[0025] According to some embodiments of the invention, OH - / SiO2=0.1~0.3.
[0026] According to some embodiments of the present invention, R1 / SiO2=0.1-0.3.
[0027] According to some embodiments of the present invention, I / SiO2=20-60.
[0028] According to some embodiments of the present invention, mR2 / mSiO2=0.1-0.25.
[0029] According to some embodiments of the present invention, the crystallization treatment is performed at a temperature of 100 to 200° C., preferably 140 to 180° C., and for a time of 2 to 200 hours, preferably 24 to 72 hours.
[0030] According to some embodiments of the present invention, the calcination temperature is 400-700° C., preferably 500-600° C.; the calcination time is 0.5 h-8 h, preferably 4-6 h.
[0031] According to some embodiments of the present invention, the calcining is performed in air.
[0032] According to some embodiments of the present invention, the mixture is crystallized, cooled, filtered, washed, dried, and then calcined.
[0033] According to some embodiments of the present invention, the drying temperature is 30 to 200° C., preferably 80 to 120° C., and the drying time is 3 to 36 hours, preferably 3 to 24 hours.
[0034] In a second aspect, the present invention provides a ZSM-5 molecular sieve prepared by the preparation method described in the first aspect.
[0035] According to some embodiments of the present invention, the ZSM-5 molecular sieve has a multi-level pore structure including micropores and mesopores.
[0036] According to some embodiments of the present invention, the size of the mesopores is 3 to 20 nm.
[0037] According to some embodiments of the present invention, the mesopore volume of the ZSM-5 molecular sieve is ≥0.05 cm3 g -1 .
[0038] According to some embodiments of the present invention, the mesopore volume of the ZSM-5 molecular sieve is greater than 0.08 cm 3 g -1 .
[0039] According to some embodiments of the present invention, the mesopore volume of the ZSM-5 molecular sieve is 0.15 to 0.30 cm 3 g -1 .
[0040] In a third aspect, the present invention provides application of the ZSM-5 molecular sieve described in the second aspect in the field of catalysts.
[0041] The beneficial effects of the present invention are at least:
[0042] (1) The single crystal multi-level pore ZSM-5 molecular sieve provided by the present invention has more mesopores than the traditional ZSM-5 molecular sieve, thereby improving the diffusion shape selectivity of the molecular sieve micropores and enhancing the accessibility of the acid sites of the ZSM-5 molecular sieve.
[0043] (2) The mesopores in the ZSM-5 molecular sieve provided by the present invention are generated during the hydrothermal synthesis process, thereby avoiding the adverse effects of the subsequent alkali treatment to generate mesopores on the molecular sieve skeleton structure, facilitating the preparation of a ZSM-5 molecular sieve with a mesoporous structure having stable quality, and effectively saving costs.
[0044] (3) The mesopores in the ZSM-5 molecular sieve provided by the present invention are mainly formed inside the single crystals. Compared with the mesopores formed between the single crystals, the multi-level pore structure composed of micropores and mesopores can have better connectivity, so that the ZSM-5 molecular sieve has better mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the XRD diffraction pattern of the ZSM-5 molecular sieve prepared in this Example 1.
[0046] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution diagram of the ZSM-5 molecular sieve prepared in Example 1.
[0047] Figure 3 This is a transmission electron microscope photograph of the ZSM-5 molecular sieve prepared in Example 1. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0050] In each embodiment and comparative example of the present invention, the test method adopted is as follows:
[0051] XRD phase analysis was performed using a Bruker D8Focus diffractometer with a graphite monochromator, a Cu target Kα ray light source, a wavelength λ of 0.154 nm, a tube voltage of 40 kV, a tube current of 40 mA, and recording diffraction signals in the 2θ range of 3-90° (scanning speed of 2° / min).
[0052] The specific surface area and pore volume were analyzed by low-temperature N2 adsorption-desorption analysis of the samples using a Tristar3000 specific surface analyzer produced by Micrometrics. The samples were pretreated at 300°C for 6 hours by vacuum activation before testing, and the test temperature was -196°C. The specific surface area, pore volume and other pore structure data of the test samples were obtained by analyzing the isotherms.
[0053] Transmission electron microscopy images were taken using a FEI Tecnai 20S-Twin microscope.
[0054] Example 1
[0055] Sodium hydroxide and sodium aluminate were dissolved in deionized water, and then n-butylamine (R1) was added. After stirring evenly, silica sol was added and stirred at 40°C for 3 hours to obtain a uniform colloid. The molar ratio of the mixed system was: SiO2: 0.016Al2O3: 0.2R1: 0.25NaOH: 45H2O; poly (allylamine) (R2, M W =17500) and stirred evenly, mR2 / mSiO2=0.2; the colloid was placed in a polytetrafluoroethylene-lined pressure steel autoclave and crystallized at 180°C for 72 hours. After the crystallization, it was naturally cooled to room temperature, the crystallized product was filtered, washed, and dried, and finally calcined at 550°C in air for 5 hours to remove the template agent used, thereby obtaining a ZSM-5 molecular sieve, which is recorded as A1.
[0056] Figure 1 The XRD diagram of the product prepared in this example shows a clear MFI structural characteristic diffraction peak, indicating that the product is a ZSM-5 molecular sieve.
[0057] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution diagram of the molecular sieve prepared in this example show an obvious hysteresis loop in the relative pressure range of p / p0 of 0.45 to 1.0, indicating that the molecular sieve has a mesoporous channel structure with a mesopore size of 3 to 10 nm.
[0058] Figure 3 This is a transmission electron microscope photograph of the molecular sieve prepared in this example. It can be seen that the molecular sieve has a multi-level pore structure, and the mesoporous structure is located inside the single crystal.
[0059] Example 2
[0060] The preparation method of the molecular sieve refers to Example 1, except that the molar ratio of the mixed system is: SiO2: 0.03Al2O3: 0.15R1: 0.2NaOH: 55H2O.
[0061] Example 3
[0062] The molecular sieve preparation method refers to Example 1, with the only difference being that: mR2 / mSiO2=0.3.
[0063] The obtained ZSM-5 molecular sieve is recorded as A3.
[0064] Example 4
[0065] The molecular sieve preparation method refers to Example 1, with the only difference being that: mR2 / mSiO2=0.15.
[0066] The obtained ZSM-5 molecular sieve is recorded as A4.
[0067] Example 5
[0068] The method for preparing the molecular sieve is similar to that of Example 1, except that mR2 / mSiO2=0.1.
[0069] The obtained ZSM-5 molecular sieve was recorded as A5.
[0070] Example 6
[0071] The molecular sieve preparation method refers to Example 1, with the only difference being that: mR2 / mSiO2=0.05.
[0072] The obtained ZSM-5 molecular sieve was recorded as A6.
[0073] Example 7
[0074] The molecular sieve preparation method is similar to that in Example 1, except that: W = 17500 poly (allylamine) replaced by M W = 15000 poly (allylamine).
[0075] The obtained ZSM-5 molecular sieve was recorded as A7.
[0076] Example 8
[0077] The molecular sieve preparation method is similar to that in Example 1, except that: W = 17500 poly (allylamine) replaced by M W =65000 poly(allylamine).
[0078] The obtained ZSM-5 molecular sieve was recorded as A8.
[0079] In this embodiment, since the molecular weight of the mesoporous template used is too large, the particles of the synthesized molecular sieve A8 are very small, the crystallinity is reduced, and the intracrystalline mesopores are reduced.
[0080] Example 9
[0081] The molecular sieve preparation method is similar to that of Example 1, except that n-butylamine is replaced with an equimolar amount of tetrapropylammonium bromide.
[0082] The obtained ZSM-5 molecular sieve was recorded as A9.
[0083] Example 10
[0084] The molecular sieve preparation method is similar to that of Example 1, except that n-butylamine is replaced with an equimolar amount of tetrabutylammonium hydroxide.
[0085] The obtained ZSM-5 molecular sieve was recorded as A10.
[0086] Embodiment 11
[0087] The molecular sieve preparation method is similar to that in Example 1, except that: W = 17500 of poly (allylamine) was replaced by cetyltrimethylammonium bromide (CTABr).
[0088] The obtained ZSM-5 molecular sieve was recorded as A11.
[0089] Example 12
[0090] The molecular sieve preparation method is similar to that in Example 1, except that: W = 17500 poly (allylamine) replaced by hexyltrimethylammonium bromide (HTAB)
[0091] The obtained ZSM-5 molecular sieve was recorded as A12.
[0092] Comparative Example 1
[0093] Sodium hydroxide and sodium aluminate were dissolved in deionized water, and then n-butylamine (R1) was added. After stirring evenly, silica sol was added and stirred at 40°C for 3 hours to obtain a uniform colloid with a molar ratio of SiO2: 0.016Al2O3: 0.2R1: 0.25NaOH: 45H2O. The colloid was placed in a polytetrafluoroethylene-lined pressure steel autoclave and crystallized at 180°C for 72 hours. After the crystallization was completed, it was naturally cooled to room temperature, and the crystallized product was filtered, washed, and dried. Finally, it was calcined in air at 550°C for 5 hours to remove the template used, and a ZSM-5 molecular sieve with only a microporous structure was obtained, which was recorded as B1.
[0094] Comparative Example 2
[0095] Sodium hydroxide and sodium aluminate were dissolved in deionized water, and then n-butylamine (R1) and poly(allylamine) (R2, M W =17500), stir evenly and then add silica sol, stir at 40℃ for 3h to obtain a uniform colloid, the molar ratio of the mixed system is: SiO2: 0.016Al2O3: 0.2R1: 0.25NaOH: 45H2O, mR2 / mSiO2=0.2; the colloid is placed in a polytetrafluoroethylene-lined pressure steel autoclave and crystallized at 180℃ for 72h. After the crystallization is completed, it is naturally cooled to room temperature, the crystallized product is filtered, washed, and dried, and finally calcined in air at 550℃ for 5h to remove the template used to obtain ZSM-5 molecular sieve, recorded as B2.
[0096] Evaluation of N2 adsorption and desorption performance of molecular sieve
[0097] The N2 adsorption and desorption data of the molecular sieves prepared in each embodiment and comparative example are shown in Table 1:
[0098] Table 1 Molecular sieve N2 adsorption and desorption data
[0099]
[0100]
[0101] The relative crystallinity is calculated by taking sample A1 as the standard sample, relative crystallinity = (sample characteristic equal area / standard sample characteristic peak area) × 100%; the average particle size is calculated from XRD data; S BET represents the specific surface area, V total represents the total pore volume, V micro represents the micropore volume, V mes represents the mesopore volume.
[0102] Molecular sieve strength performance evaluation
[0103] The molecular sieves prepared in each embodiment and comparative example are molded, and the molding method is as follows:
[0104] Weigh 5wt% of sesbania powder, 30wt% of aluminum oxide, and 3wt% of nitric acid aqueous solution (50wt%) of the molecular sieve, mix with the molecular sieve and an appropriate amount of water, extrude strips, and dry to obtain a molded sample.
[0105] The wear rate of the formed sample is measured by a wear tester, the rotation speed of the wear tester is 25r / min, and the grinding time is 40min. The lower the wear rate, the better the mechanical strength of the sample.
[0106] The wear rate is expressed as mass percentage m (%) and is calculated according to the following formula:
[0107] m = (weight of weighing bottle plus sample - weight of weighing bottle plus sample after grinding) / sample weight Test the abrasion rate twice under the same test conditions and take the average of the two test results. The wear rate test results are shown in Table 2.
[0108] Table 2 Molecular sieve attrition rate data
[0109]
[0110] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a ZSM-5 molecular sieve, characterized in that: include: S1. Obtaining a colloid including an aluminum source, an alkali source, a silicon source, a microporous template, and a solvent; S2. adding a mesoporous template to the colloid to obtain a mixture; S3. The mixture is crystallized and calcined to obtain a ZSM-5 molecular sieve.
2. The preparation method according to claim 1, characterized in that: The microporous template agent is selected from at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetrabutylammonium hydroxide and n-butylamine, preferably n-butylamine; And / or, the mesoporous template agent is poly(allylamine), preferably, the weight average molecular weight M of the poly(allylamine) is w It is 10,000 to 70,000, preferably 10,000 to 50,000, more preferably 10,000 to 30,000, and further preferably 12,000 to 20,000.
3. The preparation method according to claim 1 or 2, characterized in that: The aluminum source is selected from at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide; And / or, the alkaline source is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water; And / or, the silicon source includes at least one of silicon powder, silicon spheres, silica gel, silica sol, sodium silicate, silica alumina, silicate, silicon tetrachloride, silane, white carbon black, and diatomaceous earth; And / or, the solvent includes at least one of water, methanol, ethanol, ethylene glycol, and glycerol.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as OH - The microporous template agent is R1, the mesoporous template agent is R2, the solvent is I, and the molar ratio of each raw material is: SiO2 / Al2O3=25-300, OH - / SiO2=0.05~0.5, R1 / SiO2=0.01~0.8, I / SiO2=3~300; the mass ratio of the mesoporous template agent to the silicon source is mR2 / mSiO2=0.01~0.
8.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The crystallization treatment is performed at a temperature of 100 to 200° C. and for a time of 2 to 200 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The calcination temperature is 400-700°C and the calcination time is 0.5h-8h; And / or, the calcination is carried out in air.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixture is crystallized, cooled, filtered, washed, dried and then calcined.
8. A ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 7.
9. The ZSM-5 molecular sieve according to claim 8, characterized in that: The ZSM-5 molecular sieve has a multi-level pore structure including micropores and mesopores; Preferably, the size of the mesopores is 3 to 20 nm.
10. Use of the ZSM-5 molecular sieve according to claim 8 or 9 in the field of catalysts.